2020
DOI: 10.4314/bcse.v34i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural, spectral and biological evaluation of metals endowed 1,2,4-triazole

Abstract: Biologically active triazole Schiff base ligand 2,4-dichloro-6-[(1H-1,2,4-triazol-3-ylimino)methyl]phenol (A) has been synthesized by the condensation reaction of an equimolar amount of 1H-1,2,4-triazole-3-amine and 3,5-dichlorosalicylaldehyde and then it coordinated with salts of metals [VO(IV), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II)] in 2:1 molar ratio to derive a series of transition metal chelates (1)-(6). All the compounds were characterized by various physical, spectral, analytical techniques and elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The as-synthesized metal-based thiazole Schiff base ligands were scrutinized for developing new antibacterial agents. The growth-inhibiting potentials of all the compounds were explored against two Gram (+) bacteria; Bacillus subtilis and Staphylococcus aureus as well as two Gram (−) bacteria; Salmonella typhimurium and Escherichia coli by standard disc diffusion method [35]. Streptomycin was employed as the standard antibacterial agent in this assay.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The as-synthesized metal-based thiazole Schiff base ligands were scrutinized for developing new antibacterial agents. The growth-inhibiting potentials of all the compounds were explored against two Gram (+) bacteria; Bacillus subtilis and Staphylococcus aureus as well as two Gram (−) bacteria; Salmonella typhimurium and Escherichia coli by standard disc diffusion method [35]. Streptomycin was employed as the standard antibacterial agent in this assay.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Many studies have revealed the considerable chemical and biological importance of the electron lone pair of nitrogen's imine group [6]. This group can be considered crucial for Schiff base exploitation in biology and various branches of chemistry and reactions [7][8][9]. For example, in the coordination chemistry, Schiff bases have the ability to act as ligands and chelate with metals through the nitrogen in the imine group and an adjacent donor atom such as nitrogen, sulfur, and oxygen [10][11][12][13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…This protein was selected due to their reported studies [17,18], which revealed that theses complexes can bind to the DNA gyrase and could be considered as biologically active compound [19]. Additionally, the synthesized complexes were screened in vitro for antimicrobial activity and were subjected to theoretical molecular docking evaluation [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%